With a farewell to mother and highlighting some milestones, we present this issue of AyR - Farías, Miguel (Árboles y Rizomas, 2025)
The editor-in-chief pays a heartfelt tribute to his mother who passed away while the final edition of this issue was being prepared. The figure of the mother is highlighted with references to Nicanor Parra’s and Pablo Neruda’s tributes to Violeta Parra. Next, we review some recent intellectual milestones relevant to the editorial policies of open access journals committed to open science. The first relates to funding cuts for research in key areas of the humanities carried out by the United States government. The second reports that in France, the National Center for Scientific Research will suspend access to Web of Science following a change in research evaluation policies from quantitative bibliometric indicators to qualitative, open, and transparent evaluations. The third milestone highlighted is the publication of the Cervantes Institute Yearbook (2025), El español en el mundo (Spanish in the World), which mentions that Spanish now reaches 635 million users worldwide, ranking just below Mandarin Chinese and Hindi. The dossier commemorating the 80th anniversary of Gabriela Mistral’s Nobel Prize is announced, and the works included in the miscellaneous section are reviewed.